Host Genotype and Tissue Type Determine DWV Infection Intensity - Penn, Hannah J.; Simone-Finstrom, Michael; Lang, Sarah; Chen, Judy; Healy, Kristen (Frontiers in Insect Science, 2021)
Varroa mite-vectored viruses such as Deformed wing virus (DWV) are of great concern for honey bee health as they can cause disease in individuals and increase colony mortality. Two genotypes of DWV (A & B) are prevalent in the United States and may have differential virulence and pathogenicity. Honey bee genetic stocks bred to resist Varroa mites also exhibit differential infection responses to the Varroa mite-vectored viruses. The goal of this project was to determine if interactions between host genotype could influence the overall infection levels and dissemination of DWV within honey bees. To do this, we injected DWV isolated from symptomatic adult bees into mite-free, newly emerged adult bees from five genetic stocks with varying levels of resistance to Varroa mites. We measured DWV-A and DWV-B dissemination among tissues chosen based on relevance to general health outcomes for ten days. Injury from sham injections did not increase DWV-A levels but did increase DWV-B infections. DWV injection increased both DWV-A and DWV-B levels over time with significant host stock interactions. While we did not observe any differences in viral dissemination among host stocks, we found differences in virus genotype dissemination to different body parts. DWV-A exhibited the highest initial levels in heads and legs while the highest initial levels of DWV-B were found in heads and abdomens. These interactions underscore the need to evaluate viral genotype and tissue specificity in conjunction with host genotype, particularly when the host has been selected for traits relative to virus-vector and virus resistance.